Hemorrhagic, Hemostatic, and Thromboelastometric Disorders in 35 Dogs with a Clinical Diagnosis of Leptospirosis: A Prospective Study. (2nd December 2016) - Barthélemy, A.; Magnin, M.; Pouzot‐Nevoret, C.; Bonnet‐Garin, J.‐M.; Hugonnard, M.; Goy‐Thollot, I.
Abstract : Background: Leptospirosis in dogs is occasionally associated with a hemorrhagic syndrome, the pathophysiology of which is not fully understood. Hypothesis/Objectives: To characterize hematologic, hemostatic, and thromboelastometric abnormalities in dogs with leptospirosis and to study their association with hemorrhagic diatheses and outcomes. Animals: Thirty‐five client‐owned dogs. Methods: A prospective observational single cohort study was conducted. Results from the CBC, coagulation tests (prothrombin, activated partial thromboplastin and thrombin times, fibrinogen, fibrin(ogen) degradation products, and D‐dimer concentrations), rotational thromboelastometry (TEM), signalment, hemorrhagic diatheses, occurrence of disseminated intravascular coagulation (DIC) at admission, and survival to discharge were recorded. Results: The most common hematologic and hemostatic abnormalities were anemia (30/35), thrombocytopenia (21/35), and hyperfibrinogenemia (15/35). Eight dogs were diagnosed with DIC. A normal TEM profile was found in 14 dogs, a hypercoagulable profile in 14 dogs, and a hypocoagulable profile in 7 dogs. The 8 dogs with hemorrhagic diatheses at admission had significantly decreased platelet counts ( P = .037) and increased D‐dimer concentrations ( P = .015) compared with other dogs. Dogs with a hypocoagulable profile exhibited more hemorrhagic diatheses compared with the dogs that had normal and hypercoagulable profiles ( P = .049). The mortality rate was lower in dogs with a hypercoagulable profile than in those with a hypocoagulable profile (21% vs 57%; P = .043). Disseminated intravascular coagulation was not a significant prognostic factor. Conclusions and Clinical Importance: Thromboelastometric parameters were altered in dogs with both hypercoagulable and hypocoagulable profiles. A hypocoagulable profile was significantly correlated with hemorrhagic diathesis and higher mortality rate.